Physics contributionsComparison and verification of the reconstruction method of the catheters for interstitial brachytherapy - Błasiak, Barbara; Zwierzchowski, Grzegorz; Skowronek, Janusz; Stefaniak, Patrycja; Dymnicka, Magdalena (Journal of Contemporary Brachytherapy, 2009)
Purpose: 1. Comparison and verification of accuracy of the implant reconstruction method based on images from IBU and CT. 2. Estimation of influence of the implant reconstruction method on dose disposition in selected reference points. Material and methods: Paraffin-wax phantom with three catheters, central marker and control point were prepared. IBU unit were used for obtaining two series of images for reconstruction. The Earth magnetic field correction algorithm was used to correct S-shape distortions of the images. CT images (1 mm slice) were prepared. In the treatment planning system positions of 15 catheter points (MP, measure points), control point (CP) and central marker (CM) were reconstructed for each series of images. Distances between 15 catheter points and control point, and between catheter points and central marker were calculated. Results: There were no statistically significant differences observed for IBU and CT based reconstructions for all orientations of the phantom (p > 0.05, U-Mann Whitney Test). There were no statistically significant differences observed between reconstruction based on IBU images with and without Earth magnetic field correction algorithm for phantom located perpendicular to the IBU table (p > 0.05, Wilcoxon Test). Statistically significant differences were observed only for images set with long axis of the phantom located parallel to the table (p < 0.05, Wilcoxon Test). There were no statistically significant differences observed for values doses in reference points for reconstruction based on IBU images and CT for all orientations of the phantom. Conclusions: 1. Obtained results showed that IBU (radiographs based) reconstruction of the catheter placement is the reliable and accurate method for interstitial implants when reconstruction based on CT “catheter tracking” is not possible or not necessary. 2. The Earth magnetic field correction algorithm should be always use to correct S-shape distortions; reconstruction will be more accurate in particular orientations of image intensifier of the imaging unit.